Comparative Study Between Silver Nanoparticles Dressing (SilvrSTAT Gel) and Conventional Dressing in Diabetic Foot Ulcer Healing: A Prospective Randomized Study. (March 2023) - Essa, Mohamed S.; Ahmad, Khaled S.; Zayed, Mohamed E.; Ibrahim, Samia G.
Background: We are trying to evaluate silver nanoparticles' effectiveness (SilvrSTAT Gel) in accelerating healing rate of nonischemic diabetic foot ulcers (DFUs). Methods: This prospective, double-blind, randomized, controlled study includes 80 patients with nonischemic DFUs classified into 2 groups. Group A was subjected to SilvrSTAT Gel dressing, and group B was subjected to conventional dressing (wet-to-moist dressing with or without povidone-iodine). All cases had minimal debridement before treatment. In both groups, all cases were nonischemic after successful revascularization either by bypass surgery or endovascular therapy. Results: The healing rate of the SilvrSTAT group was significantly higher than that of the conventional group. The healing rate per week of the SilvrSTAT group was considerably higher than that of the conventional group ( P < .0001). The rate of complete healing for ulcers in group A was achieved in 22 patients (55%) by the 6th week, while 29 (72.5%), 34 (85%), and 36 (90%) patients were healed entirely by the 8th, 10th, and 12th weeks, respectively. In group B: 20 (50%), 27 (67.5%), and 30 (75%) patients were completeley healed by the 8th, 10th, and 12th weeks, respectively. Conclusions: SilvrSTATGel is effective in the treatment of DFU.